AB0986 Management of osteoporosis after major fracture in a cohort of women aged over 50 in a real life setting. (12th June 2018) - Nutz, A.; Bastide, S.; Flaisler, F.; Gaujoux-Viala, C.
Abstract : Background: Osteoporosis is the most common metabolic bone disease. Fractures constitute a major health concern because prior fractures are associated with an increased risk of subsequent fracture. Moreover, osteoporotic fractures have been associated with increased mortality risk. 1 Hence secondary fracture prevention is recommended. Anti-osteoporotic drugs are available, but in the last decade an alarming decrease of anti-osteoporotic therapy use was observed. 2 Objectives: The objective of this study was to analyse the management of osteoporosis after major fracture (hip, vertebral and humerus fractures) in women aged over 50 in a real life setting. Methods: We conducted an observational study on all women over 50 years of age who experienced a major fracture at Nîmes University Hospital in 2015 identified by informatic codes. Only fragility fractures were included. Data collected prospectively in the computerised medical files were extracted: prescription of a post-menopausal osteoporosis therapy; therapy initiation; prescription and completion of generalised bone mineral density testing; and prescription and completion of blood sample tests to look for secondary osteoporosis. We also recorded the department in which the hospitalizations occurred and the fracture localization. Results: Of 375 women over 50 with a registered fracture in 2015, 264 were included. The exclusion criteria were women with traumatic fracture or minor osteoporotic fracture. The median age was 84 years old. The most common major fractures were hip (52.3%), humerus (20.8%) and spine (18.9%). Forty-five (17.0%) patients had experienced a fracture prior to the 2015 fracture. Only 12 patients (4.5%: IC95%[2.4–7.8]) had an anti-osteoporotic drug prescription at the end of the hospitalisation and only 45 women (17%) had anti-osteoporotic drug prescription planned later. The median period until anticipated prescription was 9 days and the median period until prescription in practice was 18 days. Assessment of bone mineral density was planned later in only 23 patients (8.7%: IC95% [5.6–12.8]). Blood sample tests were realised in 49 women (18.6%: IC95% [14.1–23.8]). In surgical department, anti-osteoporotic drug prescription was planned in only 3 women (1.5%) compared with 40 women (56.3%) in medical departments. Conclusions: A large majority of women with osteoporotic major fracture are not receiving appropriate therapy and recommended management in 2015 in Nîmes University Hospital. The rate is dependent on the department in which patients are hospitalised. The results of our study highlight the urgent need for optimisation of osteoporotic fracture management, especially in the surgical department. References: [1] Katsoulis M, Benetou V, Karapetyan T, Feskanich D, Grodstein F, Pettersson-Kymmer U, et al. Excess mortality after hip fracture in elderly persons from Europe and the USA: the CHANCES project. J Intern Med. 2017Mar;281(3):300–10. [2] Van der Velde RY, Wyers CE, Teesselink E, Geusens PPMM, van den Bergh JPW, de Vries F, et al. Trends in oral anti-osteoporosis drug prescription in the United Kingdom between 1990 and 2012: Variation by age, sex, geographic location and ethnicity. Bone. 2017;94:50–5. Disclosure of Interest: None declared